A Comparative Analysis of Methods for Quantitation of Sugars during the Corn-to-Ethanol Fermentation Process. (October 2020) - Bilskey, Sarah R.; Olendorff, Samantha A.; Chmielewska, Karolina; Tucker, Kevin R.
The quantitation of sugars, including glucose, the primary fermentable sugar; maltose (DP2); and maltotriose (DP3), is a standard procedure during the corn-to-ethanol fermentation process. The quantitation of glucose by the Megazyme Assay utilizing glucose oxidase and peroxidase enzymes (GOPOD) and UV-Vis detection, high-performance liquid chromatography with refractive index detection (HPLC-RID), and liquid chromatography mass spectrometry (LC-MS) with electrospray ionization (ESI) and selected ion monitoring (SIM) was studied. Three biological flask fermentation replicates were analyzed every 12 h beginning at 14 h of fermentation (T14) until near completion of fermentation (T62). The method comparison results for glucose quantitation showed that the LC-MS SIM analysis had the lowest limit of quantitation (LOQ) at 2 ppm and the widest dynamic range of 2.7 orders of magnitude. The HPLC-RID analysis had a linear dynamic range (LDR) of 1.5 orders of magnitude with an LOQ of 1500 ppm. The Megazyme GOPOD analysis had an LDR of 0.9 orders of magnitude with an LOQ of 120 ppm. The HPLC-RID method was ideal for glucose quantitation when it was present in high concentrations. In contrast, maltose and maltotriose components were found to be present in lower concentrations, such that simultaneous quantitation of the three analytes is difficult during fermentation. The LC-MS method was the only method able to quantify the concentration of glucose successfully and simultaneously with DP2 and DP3 in all the fermentation broth samples collected from T14 through T62 during the corn-to-ethanol fermentation process.